A combined X-ray spectroscopic study on the multicolored pattern formation in gels containing FeCl3 and K3[Fe(CN)6]. Issue 4 (8th February 2016) - Hayashi, Hisashi; Abe, Hitoshi
Abstract : We examined the potential of the combined use of time-resolved XRF and position-dependent XANES, for the study of intricate reaction–diffusion processes of inorganic compounds in gel media. Abstract : We examined the potential of the combined use of two X-ray spectroscopic methods, time-resolved X-ray fluorescence (XRF) spectroscopy and position-dependent X-ray absorption near-edge structure (XANES) spectroscopy, for the study of intricate reaction–diffusion processes of inorganic compounds in gel media. To test this approach, we prepared a glass tube containing agarose gel mixed with FeCl3 solution and water-glass gel mixed with K3 [Fe(CN)6 ] solution and hydrochloric acid. Wide brown and narrow blue bands formed in the water-glass gel, and the full development of the colored patterns took approximately 25 days. XRF and XANES spectroscopies were then used to study the time dependence of the Fe concentration distributions and the microscopic local structures of the Fe species formed in the colored bands, respectively. From these analyses, it was deduced that the brown bands were formed by the stable accumulation of Fe species whose local structure was mainly [Fe(Cl)2 O4 ]; in contrast, the formation of the blue bands (originating from Prussian blue (PB) like compounds) was largely insensitive to both the Fe concentration distribution and the local structure of the dominant Fe species (mainly [Fe(Cl)O5 ]) in the bands. Such insensitivities are attributable to the extremely small solubility product of PB (∼10 −41 ), which allows PB/PB-like compounds to form even under very low concentrations of both Fe 2+ and [Fe(CN)6 ] 3+ . As a result, the brown bands were obscured by the blue colored PB-like compounds when high concentrations of Fe 2+, [Fe(CN)6 ] 3+, and/or [Fe(CN)6 ] 4+ were present, but became visible to reveal multicolored patterns under very low concentrations of these ions.